Crystallin β-b2 promotes retinal ganglion cell protection in experimental autoimmune uveoretinitis - Bauer, Dirk; Böhm, Michael R. R.; Wu, Xiaoyu; Wang, Bo; Jalilvand, Tida Viola; Busch, Martin; Kasper, Maren; Brockhaus, Katrin; Wildschütz, Lena; Melkonyan, Harutyun; Laffer, Björn; Meyer Zu Hörste, Gerd; et al. (Frontiers in Cellular Neuroscience, 2024)
Crystallin b2 (crybb2) is upregulated in regenerating retinas and in various pathological conditions of the retina, including uveoretinitis. However, the role of crybb2 in this disease is largely unknown. Therefore, we used recombinant crybb2 (rcrybb2) as intravitreal treatment of B10.RIII mice prior to immunization with human interphotoreceptor retinoid-binding protein peptide [161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180] in complete Freund's adjuvant (CFA) and concomitant injection of pertussis toxin (PTX) to induce experimental autoimmune uveoretinitis (EAU). In naïve mice, more beta III-tubulin (TUBB3)+ and RNA-binding protein with multiple splicing (RBPMS)+ cells were found in the ganglion cell layer of the retina than in EAU eyes, suggesting a loss of retinal ganglion cells (RGC) during the development of EAU. At the same time, the number of glial fibrillary acidic protein (GFAP)+ cells increased in EAU eyes. RGCs were better protected in EAU eyes treated with rcrybb2, while the number of GFAP+ cells decreased. However, in retinal flatmounts, both retinal ganglion cells and retinal endothelial cells stained positive for TUBB3, indicating that TUBB3 is present in naïve B10.RIII mouse eyes not exclusive to RGCs. A significant decline in the number of RBPMSpositive retinal ganglion cells was observed in retinal flatmounts from EAU retinas in comparison to naïve retinas or EAU retinas with intravitreal rcrybb2 treatment. Whereas no significant decrease in TUBB3 levels was detected using Western blot and RT-qPCR, glial fibrillary acidic protein (GFAP) level, as a marker for astrocytes, increased in EAU mice compared to naïve mice. Level of Bax and Bcl2 in the retina was altered by treatment, suggesting better cell survival and inhibition of apoptosis. Furthermore, our histologic observations of the eyes showed no change in the incidence and severity of EAU, nor was the immune response affected by intravitreal rcrybb2 treatment. Taken together, these results suggest that intravitreal injection of rcrybb2 reduces retinal RGC death during the course of EAU, independent of local or systemic autoimmune responses. In the future, treating posterior uveitis with rcrybb2 to protect RGCs may offer a promising novel therapeutic strategy.